Using work scale safety (WSS) to determine factors influencing safety behavior among auxiliary police - Mohd Fahmi, Md Radzi (2017)
Job safety is closely related to the behavior of an individual in carrying out the work done is closely related to productivity, reputation and profitability. Many of the factors that contribute to accidents at work and it should be given serious attention due to the study of the behavior of safety is the biggest contributor to accidents that happen in the industry. Objective study was conducted to determine the factors that affect the safety behavior among Auxiliary Police. More attention has been focused on the safety behavior among Auxiliary Police in compliance with the workplace safety than determining actual hazardous scope of work and finding effective measures to reduce accident at workplace. Analyzed may be applicable procedures and policies, co-worker safety, safety communication and management safety practices. All these variables will later be seen in the perception of safety in the workplace and the impact is found safety habits such as designated. Measurement tool used in this study is similar to the measurement work safety scale (WSS) tool that has been adopted by research published earlier researchers. A total of 155 respondents were randomly selected for the study sample that included four variables. Quantitative methods and sampling methods using availability sampling used was applied in this research. The data gathered from survey were using Statistical Package for Social Sciences (SPSS) version 20.0. Finally, the finding of the study presented that procedures and policies, co-worker safety, safety communication, management safety practices are significantly related with safety behavior among Auxiliary Police